Plasma levels of active and total ghrelin in renal failure: a relationship with GH/IGF-I axis - Jarkovská, Zuzana; Hodková, Magdaléna; Sazamová, Magda; Rosická, Martina; Sulková, Sylvie; Marek, Josef; Justová, Vlasta; Lacinová, Zdeňka; Haluzík, Martin; Haas, Tomáš; Kršek, Michal (Growth hormone & IGF research, 2005)
Ghrelin was originally isolated from the rat stomach and significant amounts were found also in the kidney. Present study was designed to examine changes in ghrelin levels in renal failure and their relationship to the GH/IGF-I axis. Fourty patients with mild-to-severe CRF (19 men, 21 women, aged 62.5 +/- 2.2 years, BMI 27.57 +/- 0.73 kg/m(2)) and 34 healthy control subjects (17 men, 17 women, aged 60 +/- 2.6 years, BMI 27.55 +/- 0.79 kg/m(2)) were included in the study. Total ghrelin levels were significantly increased in patients with chronic renal failure (CRF) (p < 0.0001). Total ghrelin in CRF correlated positively with active ghrelin (p < 0.001), GH (p < 0.05), IGF-I (p < 0.05), free IGF-I (p = 0.0001), IGFBP-3 (p < 0.01), IGFBP-2 and -6 (p < 0.05). Active ghrelin in CRF correlated positively with IGF-I (p < 0.001), free-IGF-I (p < 0.005), IGFBP-2 (p < 0.05) and IGFBP-3 (p < 0.05). However, most of the correlation were markedly reduced and the significance disappeared after adjustment for different creatinine levels. Hemodialysis in patients with end stage renal disease (ESRD) resulted in a significant reduction of plasma total and active ghrelin (p < 0.01 and p < 0.001 respectively). In conclusion we demonstrated elevated plasma levels of total ghrelin in CRF, and a reduction of total and active ghrelin after a single course of hemodialysis in ESRD. The elevation of ghrelin levels could be caused by impaired clearance and/or metabolism of ghrelin in the kidney. We did not prove clearly significant relationship between ghrelin serum levels and parameters of GH/IGF-I axis in study subjects.
Keywords: renální insuficience; financování organizované; Animals; peptidové hormony; Insulin-Like Growth Factor I; Kidney; Female; ghrelin; IGFBP-3; Models, Statistical; Renal Dialysis; chronické selhání ledvin; dialýza ledvin; Growth Hormone; Creatine; ženské pohlaví; Time Factors; časové faktory; protein 2 vázající insulinu podobné růstové faktory; lidé; statistické modely; studie případů a kontrol; Receptors, Leptin; Kidney Failure, Chronic; Middle Aged; Financing, Organized; Insulin-Like Growth Factor Binding Protein 3; insulinu podobný růstový faktor I; Male; Case-Control Studies; receptory buněčného povrchu; Insulin-Like Growth Factor Binding Protein 2; index tělesné hmotnosti; leptinové receptory; kreatin; Ghrelin; Peptide Hormones; Receptors, Cell Surface; lidé středního věku; zvířata; mužské pohlaví; Renal Insufficiency; ledviny; Body Mass Index; růstový hormon; Humans